Ethno- medicinal and Conservation Studies on the Indigenous Vegetables in Akinyele Local Government Area of Oyo State, Nigeria - Modupe Janet Ayeni; Joshua Kayode; Christiana Olaide Oladele (Budapest International Research in Exact Sciences (BirEx) Journal, 2020)
The ethno- medicinal and conservation status of indigenous vegetables in Akinyele Local Government Area (LGA) of Oyo State, Nigeria were examined with a view to evolving strategies that will conserve them. A combination of social surveys and direct field observations was used. Farm and market surveys were conducted. Five farm settlements and three major markets were used. 10 each of farmers and vegetable vendors were randomly selected and interviewed with aid of semi-structured questionnaire matrix to obtain information on the vegetables in the farms and those sold in the markets. Results obtained suggested the existence of gender specificity in agricultural activities in the study area. Women were responsible for the cultivation, harvest and haulage of vegetables. A total of 33 vegetables belonging to 18 families were identified in the study area. 21 were sampled in farm settlements and markets, 11 in farm settlements only and 1 in market only. Not all the identified vegetables have been utilized as source of income. The family Amaranthaceae has the highest number of species and their ecological success may be attributed to the fact that they are mostly herbs, a few shrubs, under-shrubs, annual or perennial with efficient tap root system and adaptation to varieties of soil. The vegetables were sourced from diverse habits including herbs, shrub and trees. The leaf constituted the major part used for vegetables. All identified vegetables were rich in phytochemicals and used to manage an array of diseases. Strategies that could enhance continuous supply of the vegetables were proposed.